Adhesion of streptococcus mutans on tooth coloured restorative materials - Rahman, Raihaniah Abd (2016)
Currently, the application of nanotechnology has become broadly developed in aesthetic dentistry due to its nanofiller particles size which offered numerous excellent advantages such as capable in reducing the bacterial adhesion of cariogenic oral bacteria mostly of early oral colonizers of S. mutans. This initial adhesion of S. mutans on the surface of materials contributed to the biofilm formation, surface deterioration of materials and may cause dental caries. In order to restore a carious tooth, the use of composite resin and resin-modified glass ionomer cement (RMGIC) in the restoration field has been increased due to the demand for aesthetic value. Different filler sized materials such as nanofilled, microfilled and microhybrid were used to compare and evaluate the adhesion of S. mutans on these materials at several incubation times. Four materials were used in this study which were RMGICs; KetacTM N100 (nanofilled) and Fuji IITM LC (microfilled) and composites resins; FiltekTM Z350 (nanofilled) and FiltekTM Z250 (microhybrid). A microscopy study was performed which include atomic force microscopy (AFM) for evaluation of surface roughness of the incubation materials, confocal laser scanning microscopy (CLSM) for evaluation of biofilm thickness and scanning electron microscopy (SEM) for distribution observation of S. mutans on materials. Fluoride release measurement was carried out for RMGIC materials to analyse the fluoride release of the materials. In addition, bacteria growth was done to assess the growth activity of S. mutans on the tested materials. Gene expression was also performed to determine the gene expression levels of gtfB and gbpB genes. Data obtained were statistically analyzed with either Independent T-test or One-way ANOVA at significance level of p<0.05. From the result, Fuji II LC gave a significantly higher of fluoride release compared to Ketac in both storage media (p≤0.001). Both nanofilled materials gave a lower value of surface roughness while no significant difference of biofilm thickness between nanofilled and microfilled materials was shown except on day 7. RMGIC groups gave a lower S. mutans growth compared to composite resin group at all the incubation times. Nanofilled RMGIC gave significantly lower of expression levels of gtfB and gbpB gene compared to other materials p<0.05. From the results, surface roughness and fluoride release by RMGIC materials were recognized as a significant factor that affected the adhesion and accumulation of S. mutans on materials. In general, both nanofilled materials has the capability in reducing the bacterial adhesion of S. mutans compared to micron sized materials since most results in this study proved that nanofilled gave lower surface roughness, less biofilm thickness and low level of gene expression. Comparison between both nanofilled groups, Ketac showed an excellent improvement in reducing S. mutans adhesion compared to Z350 due to its fluoride release ability. These finding suggested a nanofilled RMGIC as the ideal material in reducing the accumulation of S. mutans, which could inhibit the adhesion of S. mutans on the surface materials.